ANTIMICROBIAL POTENTIAL OF LEAF EXTRACT OF NORMAL AND TISSUE CULTURED PLANTS OF ANDROGRAPHIS PANICULATA NEES - ANITHA P; GAYATHRAMMA K; TEJAVATHI D H (International Journal of Pharma and Bio Sciences, 2013)
Various extracts of root, stem and leaf of normal and tissue cultured plants of Andrographis paniculata were tested against five pathogenic bacteria. Four months old field grown and tissue cultured plants raised on MS+BAP (8.86 µM) were used as source plants. Escherichia coli, Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus and Proteus vulgaris were pathogenic bacteria tested by Agar well diffusion method. The effect of various extracts measured by zone of inhibition varies with pathogens and also the source. Comparatively, methanolic leaf extracts of tissue cultured plants showed better zone of inhibition than the normal plants against all pathogens. Enhanced antibacterial activity of extracts of tissue cultured plants is related to the better growth performance and high content of secondary metabolites than the normal plants.